Human resource development practices and organisational commitment of teachers in government aided secondary schools in Wakiso district, Uganda - Mugizi, Wilson (International Journal of Education and Social Science Research, 2019)
This study analysed human resource development (HRD) practices and organisational commitment (OC) of teachers in Government Aided Secondary Schools in Wakiso District, Uganda. Particularly, the study analysed the relationshi p between performance appraisal, training and promotion and OC. The study used a sample of 336 secondary school teachers who responded to a self-administered questionnaire. Descri ptive analysis, factor analyses, Cronbach alpha (?) tests and multi ple regression were carried out. Descri ptive analysis revealed that OC, performance appraisal and promotion were moderate while training offered was good. Factor analysis and Cronbach alpha (?) tests revealed that the items measuring HRD practices subscales were valid and reliable measures. Multi ple regression analysis revealed that performance appraisal and promotion had a positive and significant relationshi p with OC. However, the relationshi p between training and OC was negative and insignificant. It was concluded that in the context of secondary schools in Uganda, OC was problematic, the current performance appraisal and promotion approaches were insufficient but training was sufficient. Therefore, it was recommended that the Ministry of Education, Science, Technology and Sports (MoESTS) in liaison with head teachers should improve the implementation of performance appraisal, however they should not over prioritise the provision of training to teachers, and the Education Service Commission which is the body responsible for the promotion of teachers should reform the promotional practices.
Keywords: Human Resource Development Practices; Organizational Commitment; Performance Appraisal; Promotion; Training